2019
DOI: 10.1093/jxb/erz253
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical principles and models of plant growth mechanics: from cell wall dynamics to tissue morphogenesis

Abstract: Plant growth research produces a catalogue of complex open questions. We argue that plant growth is a highly mechanical process, and that mathematics gives an underlying framework with which to probe its fundamental unrevealed mechanisms. This review serves to illustrate the biological insights afforded by mathematical modelling and demonstrate the breadth of mathematically rich problems available within plant sciences, thereby promoting a mutual appreciation across the disciplines. On the one hand, we explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 94 publications
(121 reference statements)
0
35
0
Order By: Relevance
“…[Oscillatory ion movement in the electrolyte solution (Pietruszka et al 2018) accompanies the uni-directional increase in pollen tube, and changes the chemical potential (Fermi redox energy) of particular ions]. Further investigations can go along the lines clearly illustrated in Smithers et al (2019).…”
Section: Final Commentsmentioning
confidence: 99%
“…[Oscillatory ion movement in the electrolyte solution (Pietruszka et al 2018) accompanies the uni-directional increase in pollen tube, and changes the chemical potential (Fermi redox energy) of particular ions]. Further investigations can go along the lines clearly illustrated in Smithers et al (2019).…”
Section: Final Commentsmentioning
confidence: 99%
“…A recent study using onion epidermal wall concluded that tensile (in-plane) properties (elastic compliance, plastic compliance, and creep) were largely determined by the network of cellulose microfibrils within individual lamellae of this polylamellate wall, whereas the indentation (out-of-plane) properties were largely controlled by pectins, along with some contributions from the cellulose microfibril networks (Zhang et al , 2019). Such results need to be incorporated into quantitative cell wall models with both explanatory and predictive value (Smithers et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The factors partially involved in anisotropic growth are multiple and are not limited to cytoskeleton configuration. Cell elongation is mainly driven by two mechanisms: cell wall deformation by internal turgor pressure and cell wall growth mediated by enzymatic reactions [involving expansins, xyloglucan endotransglucosylase/hydrolase (XTH), and pectin-modifying enzymes (PMEs)] and favored by hormones accumulation (like auxin, gibberellins and abscisic acid; Cosgrove, 2016 ; Smithers et al, 2019 ). The latter is commonly known as the acid growth hypothesis ( Figure 1B ; Rayle and Cleland, 1992 ).…”
Section: Grasping On the Complexity Of Plant Organ Structurementioning
confidence: 99%